Study on the Effects of Weight Training and Pressure Training on the Explosive Power of Legs in Kabaddi Players - Vandana Bhudia; Dr. Jagdishchandra L. Gothi (International Journal of Scientific Research in Humanities and Social Sciences, 2025)
The objective of this research study was to analyze the effects of weight training and pressure training on the explosive power of legs in Kabaddi players. This study was limited to female Kabaddi players from Shri Kutchi Leva Patel Kanya Vidhya mandir, Bhuj. Participants were female athletes aged 13 to 18. They were divided into three groups: Group A (weight training) with 15 players, Group B (pressure training) with 15 players, and Group C (control group) with 15 players, making a total of 45 participants. The explosive power of the legs was measured using the Standing Broad Jump test. The effects of weight training and pressure training were analyzed using a One-Way Analysis of Covariance (ANCOVA), and differences among means were tested using the Least Significant Difference Post Hoc test at a significance level of 0.05. The findings showed that a structured 12-week weight training and pressure training program led to significant improvements in the participants’ leg explosive power.
Keywords: Explosive Power; Weight Training; Pressure Training